Wavelet coding design for image data compression - Khalifa, Othman Omran (Zarqa University, Jordan, 2005)
In this paper, image compression algorithms using scalar and ventor quantisation are proposed. An analysis of wavelet coefficients encoding is explained. Wavelet capability of energy compaction is shown. Also, wavelet ventor quantisation multiresolution codebook generation is discussed. General discription of the proposed image compression algorithm with its feature is presented. In addition, simulation results and comparison with other coders is shown.